Effects of parameters of particle swarm optimization algorithms on the path planning for flexible needles - Zhang,Feifan; Yu,Longfeng; Hong,Songhe; Huang,Ye; Wang,Yu; Peng,Zhenwan (PeerJ Computer Science, 2026)
Background Percutaneous puncture has wide applications in various clinical tasks. Path planning is crucial but challenging. Particle swarm optimization (PSO) algorithms are proper candidates to solve this problem and have been introduced. However, path planning errors exist and the effects of PSO parameters have not yet been studied. Methods A kinematic model was developed using the D-H method. The best combination of PSO parameters for flexible needle-path planning was obtained by the genetic algorithm with the Lord strategy. According to simulation results, an iterative PSO is proposed. Results Simulations demonstrate that the deviation was reduced to 0.017 mm on average (mostly close to zero) with optimized parameters. An accuracy of 0.001 mm can be guaranteed by proposed iterative PSO. Conclusions The optimized parameters can significantly reduce the path deviation, and provide an optimal path with a simple PSO. The proposed iterative PSO can attain superior performance while consuming less computation time.
Keywords: Flexible needle; Particle swarm optimization; Path planning; Parameter optimization